Rare Presentation of MoyaMoya Disease with Sub acute Presentation: A Case Report from Iran - Sasan nejad, Payam; Rezaei, Fateme; Bidaki, Reza; Zarepur, Ehsan (Iranian Journal of Child Neurology, 2018)
Abstract Moyamoya disease is a chronic progressive vascular disease of brain has been characterized by bilateral stenosis or occlusion of the arteries around the circle of Willis with prominent arterial collateral circulation. We introduce a patient with Moyamoya that was been misdiagnosed. We report a 16-year-old female from northeast of Iran who complained left hemiparesis and was diagnosed Moyamoya disease by brain and cervical CT-Angiography. There is still great difficulty in the diagnosis of diffuse white matter lesions and our case shows that moyamoya disease should be considered in differential diagnoses especially among young patients presenting with unexplained cerebrovascular syndromes. The CT-Angiography showed bilateral internal carotid stenosis with "puff of smoke" collateralization arising from the circle of Willis, therefore Moyamoya disease was raised.The clinical diagnosis of Moyamoya is challenging and misdiagnosis is probable. Therefore, the physicians should know this disease and think about it in patients with Juvenile stroke.